Prediction of infiltration rates of fallow and cultivated soils in Minna, Southern Guinea Savanna zone of Nigeria - EZE, P.C.; MUSA, J.J. (Journal of Soil and Water Conservation, 2023)
Measurement and modelling of soil water infiltration under field condition are crucial to management of water resources, design and execution of drainage and irrigation projects for sustainable agricultural productivity and food security. This study was carried out to determine the time required to attain equilibrium or final infiltration rate of soils of Gidan-Kwano (a sandy loam) and Shintako (a loamy sand) sites around Minna, and reduce the tedium, time and cost associated with the measurement of soil infiltration rate. Three infiltration models (Kostiakov, Horton and Philip models) were evaluated. A double-ring infiltrometer was used to measure the infiltration rates of the soils at the two sites subjected to two land use management practices (fallow and cultivated soils) in Minna, Southern Guinea savanna zone of Nigeria. Infiltration runs were conducted at 0, 4, 8 and 12 weeks after cultivation. Results showed that the equilibrium infiltration rate of the tested soils was attained between 1 and 2 hours. The equilibrium infiltration rates of the fallow and cultivated soils were 21.54 and 7.62 cm hr-1, respectively, at the Gidankwano site, while the values at the Shintako site were 30.59 and 24.50 cm hr-1, respectively for the fallow and cultivated soils. Generally, the soils under fallow exhibited higher infiltration rates than cultivated ones. Curvefitting was done on Kostiakov’s, Horton’s and Philip’s infiltration models. Infiltration data generated using Kostiakov’s model were not significantly different from field-measured values at 5 % level of probability. The Kostiakov model was the most suitable for the prediction of infiltration rates of the soils investigated compared to Philip and Horton models. It is therefore, recommended for the soils tested, in the Southern Guinea savanna zone of Nigeria.